Interpretasi Wastra Lampung Tapis Raja Medal dalam Hermeneutika Nusantara: Indonesia - Hadi Kurniawan; Djuniwarti; Yoga Matin Albar (Universitas Negeri Jakarta, 2025)
The purpose of this study is to interpret the decorative motifs of the Tapis Lampung Raja Medal to reveal the meaning of the text using the Nusantara hermeneutic theory approach. This study uses a qualitative descriptive method through the Nusantara hermeneutic theory approach, namely ma'nā-cum-maghzā from Sahiron Syamsudin. The results of this study reveal that the Tapis Raja Medal has a literal meaning of the text, historical and dynamic phenomenal significance. This meaning is broadly related to the relationship between leaders and people who are jointly responsible for realizing a peaceful, prosperous and faithful life in God the Universe. Interpretation of artifacts from the ancestors of Indonesian craftsmen should be done through the application of hermeneutic theory from Nusantara figures who have closer cultural ties and perspectives than those from the Western world. This can enrich the range of perspectives on interpreting the meaning and philosophy of Nusantara cultural artifacts.